catena-Poly[[triphenyltin(IV)]-mu-2-(cyclohexylaminocarbonyl)benzoat o-kappa 2 O 1:O 2] - Imtiaz, Ud-Din; Raqiqt, Ul-Rasool; Bhatti, M.H.; Ng, S.W. (International Union of Crystallography, 2010)
In the title polymeric complex, [Sn(C6H5)(3)(C14H16NO3)] (n) , adjacent triphenyltin cations are bridged by the N-cyclohexylphthalamate anion through the carboxylate and carbonyl O atoms, forming a helical chain running along the b axis. The amide N atom is a hydrogen-bond donor to the uncoordinated carboxylate O atom. The geometry at the five-coordinate Sn atom is trans-C3SnO2 trigonal-bipyramidal.